Nanofluid Dynamics in Microchannel Heat Sinks: Enhancing Thermal Performance for High-Power Density Applications - Dr. N. Ayyappan,; Thaimanavan K T R,; Quazi Taif Sadat,; Dr.R.Radhika, (The Bioscan, 2026)
The ongoing miniaturization of electronic devices and the rising demand for high-power density systems have placed unprecedented emphasis on efficient thermal management solutions. Microchannel heat sinks have emerged as a promising technology due to their ability to provide high heat transfer rates within compact footprints. However, conventional coolants often struggle to meet the thermal performance requirements in these systems, particularly under extreme operating conditions. This study investigates the dynamics of nanofluid suspensions of nanoparticles within base fluids within microchannel heat sinks and their role in enhancing thermal performance. The research emphasizes the interplay between fluid properties, channel geometry, and nanoparticle concentration, highlighting their combined effect on convective heat transfer and pressure drop characteristics. Experimental and numerical analyses were conducted to evaluate the performance of different nanofluids, including metallic and oxide-based nanoparticles, across varying Reynolds numbers and heat flux conditions. Results demonstrate that the inclusion of nanoparticles significantly improves thermal conductivity and heat transfer coefficients while maintaining manageable pumping power requirements. Additionally, the study explores the influence of nanoparticle size, shape, and volume fraction on flow behavior and thermal efficiency, providing insights into optimizing nanofluid formulations for specific microchannel configurations. A comparative assessment with traditional coolants underscores the superior performance of nanofluids, particularly in high heat flux scenarios, making them suitable candidates for advanced electronic cooling applications. The findings contribute to a deeper understanding of nanofluid transport phenomena in confined microchannels and offer practical guidelines for designing next-generation high-performance cooling systems. This research lays the groundwork for future studies on sustainable, high-efficiency thermal management solutions for microelectronics and power-intensive devices. Keywords Nanofluids, Microchannel Heat Sinks, Thermal Performance, High-Power Density, Convective Heat Transfer